Karakteristik Serbuk Hidrolisat Protein Ikan Toman (Channa micropeltes) Sebagai Penyedap Rasa Alami - Evi Fitriyani; Ika Meydi Deviarni; Lukas Wibowo Sasongko (JURNAL GALUNG TROPIKA, 2021)
Fish protein hydrolyzate is breaking down proteins into simple peptides and amino acids through a hydrolysis process by enzymes, acids, or bases. This hydrolysis process uses toman fish (Channa micropellets) as an alternative to increase protein consumption and the nutritional quality of the product. It can be used as a base for natural flavor compounds. In addition, pineapple juice is added. The research was conducted in two stages: (1) making fish protein hydrolyzate powder; and (2) testing of color, organoleptik, water content, ash, protein, fat, carbohydrate, crude fiber, and glutamic acid. The results showed that giving pineapple juice 5% gave the best results for glutamic acid levels around 108.064 ppm, protein content 13.97%, fiber content 5.15%, fat content 0.44%, color 6.0, and texture 7. This study states that fish protein hydrolyzate powder with pineapple juice can be used as an alternative as a natural flavoring agent.